The Role of Students in Community Service Programs in Supporting the Blood Donor Program in Rural Areas - Akmal Rafif Harjono; Indra Wibowo; Arini Sabila Anjani; Wafda Awwaliyatul Mala; Andina Ulfah Suswanto; Febrianis Dea Arrusida; Dania Nurusyahriatus Syafaah; Zullu Nasya Ulfadhilah; Davina Aliffatul Mahfudzoh; Noviana Putri Pradini; Iis Yuliana Sari; Achmad Yasir; Mochammad Alvin Khoirur Ridlo; Ahmad Bayu Shofiyulloh; Nana Misrochah (Faculty of Engineering, Universitas Semarang, 2025)
The Community Service Program (KKN) provides students with the opportunity to directly contribute to society, especially in rural areas. This research aims to analyze the role of KKN-MB Posko 43 students in supporting the blood donation program in Penggaron Kidul Village, Semarang City. The research method used is descriptive qualitative with a case study approach. Data was collected through interviews, observations, and documentation during the implementation of the KKN program. The research findings show that KKN students played a significant role in raising public awareness about the importance of blood donation through intensive socialization and education. In addition, students also contributed by facilitating blood donation activities through coordination with the Indonesian Red Cross (PMI) and the local village government. The impact of this activity was reflected in the increase in the number of blood donors in the village, as well as the establishment of a sustainable blood donor community. The study concludes that the involvement of KKN students can have a positive impact on the sustainability of blood donation programs in rural areas, and this model is expected to be applied in other regions.